Design of a master power factor controller for an industrial plant with solar photovoltaic and electric vehicle chargers - Ghani A.A.; Ramachandaramurthy V.K.; Yong J.Y. (Springer Science and Business Media Deutschland GmbH, 2023)
Charging (batteries); Control systems; Controllers; Cost effectiveness; Electric power plants; Electric vehicles; Energy utilization; Gas emissions; Greenhouse gases; Industrial research; Natural resources; Photovoltaic cells; Power control; Reactive power; Renewable energy resources; Static synchronous compensators; Static Var compensators; Electric vehicle charging; Industrial facilities; Integration of renewable energies; Reactive power compensation; Reactive power compensator; Renewable energy source; Solar photovoltaic system; Synchronous condensers; Electric power system control